OXYGEN ISOTOPE EXCHANGE KINETICS BETWEEN H2O AND H4SIO4 FROM AB INITIO CALCULATIONS - Felipe M.A.; Kubicki J.D.; Rye D.M. (My University, 2004)
Oxygen isotope exchange between H2O and H4SiO4 was modeled with ab initio calculations on H4SiO4 + 7H2O. Constrained optimizations were performed with the B3LYP/6–31+G(d,p) method to determine reactants, transition states, and intermediates. Long-range solvation was accounted for using self-consistent reaction field calculations. The mechanism for exchange involves two steps, a concerted proton transfer from H4SiO4 forming a 5-coordinated Si followed by a concerted proton transfer from the 5-coordinated Si forming another H4SiO4. The 5-coordinated Si intermediate is C2 symmetric. At 298K and with implicit solvation included, the Gibbs free energy of activation from transition state theory is 66 kJ/mol and the predicted rate constant is 16 s−1. Equilibrium calculations between 298K and 673K yield αH4SiO4-H2O that are uniformly less than, but similar to, αqtz-H2O, and therefore αqtz-H4SiO4 is expected to be relatively small in this temperature range.